A study of the reading interests of freshman students of St. Scholastica's Academy, Marikina - Abad, Lilia L.; Hidalgo, Namnama P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1983)
This study arises from the librarian's need to know the reading interests of students and to meet the challenge of giving the right book to the right reader at the right time. This concern can be well met only if librarians know what reading experiences are likely to be most valuable to a particular student.
This study provides a general overview of the reading interests of 230 students enrolled at St. Scholastica's Academy, Marikina, for the school year 1981-1982. Specifically, this study was undertaken to come up with a student profile of the Scholasticans, relating such observations to their reading interests and related variables. The students' reading interests were found to be consistent with their high I.Q., high academic performance, upper middle-class value system and quality schooling. They read various types of reading materials but preferred fiction to nonfiction.
Recognizing the students' interests their parents, teachers and librarians are now obliged to give proper reading guidance and inculcate the right attitudes among these adolescents. It is the researcher's hope that this study may arouse educators at all levels of our educational system to encourage adolescents to read good books during their free time.
Mimeographed.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Books and reading for girls--Philippines--Marikina.; Reading interests--Philippines--Marikina.; St. Scholastica's Academy (Marikina).